2002
DOI: 10.1046/j.1523-1755.2002.00110.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of TGF-β1 in renal parenchymal scarring following childhood urinary tract infection

Abstract: There is an association between the TGF-beta1 -800 GA, -509 TT and Leu10-->Pro CT genotypes and the presence or absence of RPS. The low TGF-beta1 producer status of the -800 GA genotype may protect against the development of a pro-fibrotic pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 34 publications
3
57
2
4
Order By: Relevance
“…First, the existence of the genetic heterogeneity results from the geographical environment and living habits of subject, which influence the frequency distribution of the crowd gene. Some studies have shown that the difference in C509T gene distribution between European and Asian countries is statistically significant (Cotton et al, 2002;Holla et al, 2002;Chen et al, 2005). Second, the clinical characteristics of participants -for example, age and years from onset, male predominance -may lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…First, the existence of the genetic heterogeneity results from the geographical environment and living habits of subject, which influence the frequency distribution of the crowd gene. Some studies have shown that the difference in C509T gene distribution between European and Asian countries is statistically significant (Cotton et al, 2002;Holla et al, 2002;Chen et al, 2005). Second, the clinical characteristics of participants -for example, age and years from onset, male predominance -may lead to different outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms within the VEGF and TGF-␤1 genes have often been linked to overproduction of these proteins, and both predisposition to and sequelae of progressive renal disease (13)(14)(15). Several polymorphisms of the VEGF and TGF-␤1 genes have been identified, and there are reports on the association of TGF-␤1 gene polymorphism and renal scarring (15,16).…”
mentioning
confidence: 99%
“…Several polymorphisms of the VEGF and TGF-␤1 genes have been identified, and there are reports on the association of TGF-␤1 gene polymorphism and renal scarring (15,16). On the other hand, there is no published study on the link of VEGF gene polymorphism to renal scar formation, despite of the importance of hypoxia and angiogenesis in the scar formation.…”
mentioning
confidence: 99%
“…Solari et al (2005) documented that the risk of reflux nephropathy was higher in patients with -509CT and Leu10Pro genotypes. Khalil et al (2005) showed that homozygosity for -509T and Arg25 resulted in more rapid progression of renal failure whereas patients with -800GA genotype were less susceptible to renal scarring (Cotton et al, 2002). Numerous studies confirmed a significant participation of TGF-in pathogenesis of obstructive nephropathy (Blom et al, 2001;Chevalier, 2004;Duncan et al, 1999;Kaneto et al, 1999;Klahr & Morrissey, 1998, 2002, 2003Sato et al, 2003;Schnaper et al, 2003).…”
Section: Transforming Growth Factor (Tgf-)mentioning
confidence: 99%
“…In addition, it increases expression of TIMPs. This contributes to depressed activity of MMP and stabilization of extracellular matrix (Boettinger & Bitzer, 2002;Boettinger et al, 1997;Broder et al, 1994;Cotton et al, 2002;Deng et al, 2006;Fan et al, 1999;Goumneos et al, 2002;Guo et al, 1997;Jahnukainen et al, 2005;Korzon et al, 2004;Lane et al, 2002;Liapis, 2003). Poncelet & Schnaper (1998) documented that TGF-stimulates production of collagen I, III and IV by mesangial cells.…”
Section: Transforming Growth Factor (Tgf-)mentioning
confidence: 99%